Factors Affecting the PeduliLindungi User Experience Based on UX Honeycomb - Adhim Jati Kusuma; Pantjawati Sudarmaningtyas; Antok Supriyanto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
With background of Covid-19 pandemic, Indonesian state trying to make various efforts, so people comply health protocols. One of them is through PeduliLindungi application. PeduliLindungi has 3 main functions, namely tracing, tracking, warning and fencing. However, PeduliLindungi is deemed unable to meet user needs in terms of appearance and experience provided. This study aims to find factors that affect user experience in PeduliLindungi app based on UX Honeycomb. UX Honeycomb is a tool that can explain various aspects of user experience design in 7 indicators and grouped into 3 variables. The 3 variables are Think (useful, valuable, credible), Feel (desirable, credible), and Use (findable, accessible, usable). This study uses primary data by distributing online questionnaires to 404 respondents contains 15 statements that represent all UX Honeycomb variables, with 5 scales of answer choices namely strongly disagree/disagree/neutral/agree/strongly agree. From the calculation results, it is found that all variables and indicators significantly affect user experience with greatest level of influence being on the Think variable at 0,418, the second Use at 0,219, and the last is Feel at 0,151. Further research is expected can measure the level of influence on user experience by making direct comparisons with similar health apps.